Peri-operative management of high-risk paediatric adenotonsillectomy patients: A survey of 35 UK tertiary referral centres. (May 2017) - Cheong, Ryan Chin Taw; Bowles, Philippe; Moore, Andrew; Watts, Simon
Abstract: Introduction: Peri-operative management of high-risk paediatric patients undergoing adenotonsillectomy for treatment of obstructive sleep apnoea varies between tertiary referral hospitals. 'Day of surgery cancellation' (DoSC) rates of up to 11% have been reported due to pre-booked critical care being unavailable on the day of surgery as a result of competing needs from other hospital departments. We report the results of a survey of peri-operative management in UK tertiary care centres of high-risk paediatric patients undergoing adenotonsillectomy for obstructive sleep apnoea (OSA). Methods: An 8-point questionnaire was developed using a cloud-based software platform (www.surveymonkey.com ). A web-link to the survey was embedded in a customised e-mail which was sent via secure server to the Clinical Leads for Paediatric Otolaryngology at 35 United Kingdom (UK) Tertiary referral centres. Results: The survey response rate was 60% (n = 21). Almost all (94.1%) of centres considered paediatric critical care facilities to be limited, with 70.6% (n = 12) stating that DoSC often occurred due to unavailable paediatric critical care capacity. There was variation between tertiary referral units in the practice applied for pre-booking critical care beds (our survey identifies 6 variations) (Table 1). The most frequent selection method reported (47.1%) was at the discretion of the booking clinician at the time of listing the patient for surgery. Conclusion: In the context of limited critical care resources, variation in practice and difficulty in accurately predicting which patients will require post-operative critical care beds, a review and consensus on best practice in the peri-operative management of high risk paediatric adenotonsillectomy patients may offer a safe means of reducing cancellations and improving patient care, resource allocation and hospital efficiency.